FinnSight 2015 – A Foresight Exercise for the Shaping of National Strategies - Ville Brummer; Totti Konnola; Ahti Salo (Foresight and STI Governance)
The paper describes FinnSight 2015, the national foresight exercise of the Academy of Finland and the National Funding Agency for Technology and Innovation (Tekes), which was launched largely with the aim of informing — albeit indirectly — the development of the national strategy which is currently being implemented by establishing five Strategic Centers of Excellence in Science, and Technology. The authors analyze the policy context, management structures, methodological execution and key results of FinnSight. They also report some of the subsequent policy developments, and examine FinnSight in view of four axes of balance that are arguably helpful in the planning of foresight exercises. The methodological novelties of FinnSight are highlighted, particularly as concerns the combination of distributed work by individual panelists (which was assisted through Internet-based tools) and their interactive collaboration in group settings (which took place in facilitated workshops).